The dilemma - Paris, B. A. (New York : St. Martin's Press, 2020)
"It$1 (Bs Livia$1 (Bs 40th birthday, and her husband Adam is throwing her the party of a lifetime to make up for the wedding they never had. Everyone she loves will be there, except her daughter Marnie, who$1 (Bs studying abroad. But Livia is secretly glad Marnie won$1 (Bt be there. Livia has recently uncovered a secret about their daughter which, if revealed, will shake the foundation of their family to its core."--s
Keywords: Birthday parties -- Fiction; Mothers and daughters -- Fiction; Interpersonal relations -- Fiction; Married people -- Fiction; Birthdays -- Fiction; Family secrets -- Fiction; Thrillers (Fiction); Domestic fiction; Psychological fiction; Novels